Cerebral laterality for language is related to adult salivary testosterone levels but not digit ratio (2D:4D) in men: A functional transcranial Doppler ultrasound study. - Papadatou-Pastou, M; Martin, M (Elsevier, 2017)
The adequacy of three competing theories of hormonal effects on cerebral laterality are compared using functional transcranial Doppler sonography (fTCD). Thirty-three adult males participated in the study (21 left-handers). Cerebral lateralization was measured by fTCD using an extensively validated word generation task. Adult salivary testosterone (T) and cortisol (C) concentrations were measured by luminescence immunoassay and prenatal T exposure was indirectly estimated by the somatic marker of 2nd to 4th digit length ratio (2D:4D). A significant quadratic relationship between degree of cerebral laterality for language and adult T concentrations was observed, with enhanced T levels for strong left hemisphere dominance and strong right hemisphere dominance. No systematic effects on laterality were found for cortisol or 2D:4D. Findings suggest that higher levels of T are associated with a relatively attenuated degree of interhemispheric sharing of linguistic information, providing support for the callosal and the sexual differentiation hypotheses rather than the Geschwind, Behan and Galaburda (GBG) hypothesis.